2017
DOI: 10.1063/1.5004025
|View full text |Cite
|
Sign up to set email alerts
|

High performance broadband photodetector based on MoS2/porous silicon heterojunction

Abstract: A high speed efficient broadband photodetector based on a vertical n-MoS2/p-porous silicon heterostructure has been demonstrated. Large area MoS2 on electrochemical etched porous silicon was grown by sulphurization of a sputtered MoO3 thin film. A maximum responsivity of 9 A/W (550–850 nm) with a very high detectivity of ∼1014 Jones is observed. Transient measurements show a fast response time of ∼9 μs and is competent to work at high frequencies (∼50 kHz). The enhanced photodetection performance of the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…92 Das and coworkers boosted the detection performance of a MoS 2 /porous Si heterojunction-based photodetector by virtue of its large junction area, excellent light trapping properties, and high interfacial barrier height. 93 The photodetector exhibited an ultrahigh detectivity of approximately 10 14 Jones, small rise/fall times of 9/7 μs, and a maximum responsivity of 9 A W −1 in the range from 550 to 850 nm. In addition, a vertically standing layered MoSe 2 /p-Si heterojunction-based photodetector was also developed using graphene as the top electrode material.…”
Section: Inorganic Semiconductor/simentioning
confidence: 98%
See 1 more Smart Citation
“…92 Das and coworkers boosted the detection performance of a MoS 2 /porous Si heterojunction-based photodetector by virtue of its large junction area, excellent light trapping properties, and high interfacial barrier height. 93 The photodetector exhibited an ultrahigh detectivity of approximately 10 14 Jones, small rise/fall times of 9/7 μs, and a maximum responsivity of 9 A W −1 in the range from 550 to 850 nm. In addition, a vertically standing layered MoSe 2 /p-Si heterojunction-based photodetector was also developed using graphene as the top electrode material.…”
Section: Inorganic Semiconductor/simentioning
confidence: 98%
“…Moreover, Wang et al further fabricated vertically standing few‐layer MoS 2 /p‐Si heterojunctions with a fast response time of approximately 16 ns at zero bias . Das and coworkers boosted the detection performance of a MoS 2 /porous Si heterojunction‐based photodetector by virtue of its large junction area, excellent light trapping properties, and high interfacial barrier height . The photodetector exhibited an ultrahigh detectivity of approximately 10 14 Jones, small rise/fall times of 9/7 μs, and a maximum responsivity of 9 A W −1 in the range from 550 to 850 nm.…”
Section: D Thin Film/si Heterostructurementioning
confidence: 99%
“…Monolayer MoS 2 has been deposited by the chemical vapor deposition (CVD) method on p‐type Si to develop heterojunction solar cells . Furthermore, sulfurization of metal and metal oxide films deposited on the Si substrate has been performed to synthesize MoS 2 layers for heterostructure device applications . It has also been demonstrated that vertically standing MoS 2 ‐layered structure can be deposited directly on the Si substrate to develop optoelectronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…[28] Furthermore, sulfurization of metal and metal oxide films deposited on the Si substrate has been performed to synthesize MoS 2 layers for heterostructure device applications. [29,30] It has also been demonstrated that vertically standing MoS 2 -layered structure can be deposited directly on the Si substrate to develop optoelectronic devices. [21] In this prospect, the interface between the MoS 2 and p-type Si is the key aspect to understand the photoresponsive behavior in the heterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Among these semiconductors, Si is most widely employed, especially in complementary metal oxide semiconductor (CMOS) devices and advanced light detection systems. [6][7][8] In spite of the huge progress, it is undeniable that Si-based NIR photodetectors often suffer from relatively narrow wavelength photoresponse due to its cutoff around 1.1 µm. To address this issue, various Ge, PbS, and HgCdTe semiconductors with bandgap much smaller than that of silicon have been introduced into silicon-based NIR photodetectors.…”
mentioning
confidence: 99%